Geoelectric parameters of the northwestern part of the Ukrainian Shield from 2D inversion - I.M. Logvinov; V.N. Tarasov; I.V. Gordienko (Геофизический журнал, 2020)
Based on a 2D inversion of magnetotelluric data along six meridional profiles traversing the northwestern part of the Ukrainian shield, local objects of reduced resistivity (with ρ < 100 Ohm · m) in the Earth's crust and upper mantle are identified. The analysis of the geoelectric data makes it possible to outline the relation of conductive objects to mineral deposits with the electron type conductivity. The low resistivity objects (LRO) comparable with the in the Earth's crust deposits of most minerals with the electron-type conductivity are arranged in the Earth's crust in blocks of rocks with a resistivity of 200―1000 Ohm · m. The deposits of the platinoid group and scandium are located above very high-resistivity blocks (with resistivity exceeding 1000 Ohm · m) and are not accompanied by LRO in the Earth's crust. Within the boundaries of the North-West graphite-bearing region, most of the LRO are located in the Earth's crust depths. Relation of the LRO in the Earth’s crust and mineral deposits to nodes of fault zones active in the last 3 million years can be seen. Conductive structures in the Earth's crust of the North-Ukrainian oil and gas province (NUOP) are located in its western part outside the borders of the Ovruch graben-syncline.  At the upper mantle, conducting objects stretch from the Mozyr oil and gas region to the western part of the NUOP. The results can be used to search for mineral deposits with electron-type conductivity and to confirm the hypothesis of the role of Earth degassing and the relationship of hydrocarbon deposits to the zones of generation and transport of hydrocarbon-containing fluids.